Predictive value of preoperative serum squamous cell carcinoma antigen (SCC–Ag) level on tumor recurrence in cervical squamous cell carcinoma patients treated with radical surgery: A single-institution study. Issue 1 (January 2020) - Guo, Qinhao; Zhu, Jun; Wu, Yong; Wen, Hao; Xia, Lingfang; Wu, Xiaohua; Ju, Xingzhu
Abstract: Objective: We seek to explore the clinical significance of serum squamous cell carcinoma antigen (SCC–Ag) and the optimal cut-off value for predicting tumor recurrence and survival in operable cervical squamous cell carcinoma patients. Methods: A total of 3471 patients with cervical squamous cell carcinoma who underwent radical surgery were enrolled in this study. The cut-off value of serum SCC-Ag for tumor recurrence was calculated using the receiver operating characteristic (ROC) curve. The progression-free survival (PFS) and overall survival (OS) were analyzed by Kaplan-Meier method and multivariate analysis was further performed. Results: The optimal cut-off value of serum SCC-Ag level for predicting tumor recurrence was calculated and set at 2.75 ng/mL. Compared to the value of 1.5 ng/mL used in clinical practice, our results showed that serum SCC-Ag level >2.75 ng/mL was closely related to extrapelvic metastases in relapsed patients (P = 0.035). Multivariate analysis showed that neither serum SCC-Ag level >1.5 ng/mL nor serum SCC-Ag level >2.75 ng/mL was independent risk factors for PFS and OS in all patients. However, among 964 patients with at least one high-risk factor (parametrial invasion, vaginal margin invasion and lymph node metastasis), serum SCC-Ag level > 2.75 ng/mL, instead of serum SCC-Ag level > 1.5 ng/mL, could be used as an independent factor affecting PFS (P = 0.018). Conclusion: Preoperative serum SCC-Ag level > 2.75 ng/mL is closely related to extrapelvic recurrence, and is an independent factor for tumor recurrence and survival in cervical squamous cell carcinoma patients with high-risk factors.